2014
DOI: 10.1080/00397911.2014.883633
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Convenient Protocol for the Synthesis of 3,5-Disubstituted 1,2,4-Oxadiazoles Using HClO4-SiO2 as a Heterogeneous Recyclable Catalyst

Abstract: General experimental procedure for the synthesis of 3,5disubstituted 1,2,4-oxadiazoles (5a-5n) 3 3 Synthesis of 3,5-disubstituted 1,2 4-oxadiazoles and characterization data (5a-5n) 4 4 1 H, 13 C NMR spectra of new compounds 16 5 References 28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Nowadays, there are a few commercially available drugs containing 1,2,4-oxadiazole nucleus [ 25 ] such as pleconaril (anti-infective) [ 26 ], oxolamine (anti-inflammatory) [ 27 ], prenoxdiazine (cough suppressant), butalamine (vasodilator) [ 28 ], ataluren (use in Duchenne muscular dystrophy) [ 29 ] and proxazole (used for anti-tussive and anti-plasmodic) [ 30 ] (Fig. 2 ).…”
Section: -Oxadiazoles As Important Heterocyclic Scaffoldsmentioning
confidence: 99%
“…Nowadays, there are a few commercially available drugs containing 1,2,4-oxadiazole nucleus [ 25 ] such as pleconaril (anti-infective) [ 26 ], oxolamine (anti-inflammatory) [ 27 ], prenoxdiazine (cough suppressant), butalamine (vasodilator) [ 28 ], ataluren (use in Duchenne muscular dystrophy) [ 29 ] and proxazole (used for anti-tussive and anti-plasmodic) [ 30 ] (Fig. 2 ).…”
Section: -Oxadiazoles As Important Heterocyclic Scaffoldsmentioning
confidence: 99%
“…The reaction was completed within a very short time. From the reusability test for the particular catalyst, it was found that the catalyst can be used three times without much loss in the yield of the products (Scheme 22) [39]. The catalyst lost the water of crystallization at around 200 C. The strong acid sites of the catalyst were analyzed from the potentiometric titration curve.…”
Section: Silica-supported Acid/base Catalystsmentioning
confidence: 99%